2016
DOI: 10.1016/j.triboint.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The ability of using the cavitation phenomenon as a tool to modify the surface characteristics in micro- and in nano-level

Abstract: The aim of this paper is to investigate the possible application of the cavitation phenomenon as efficient method to modify the surface properties (e.g. the surface roughness) in the nano and micro levels. Aluminum alloy (AlSiMg) specimens were subjected to high speed submerged cavitating jets under various working conditions, for short time periods between 15 and 30 seconds. The force generated by the cavitating jet is employed to modify the surface roughness of the specimen. The target surface was analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…We demonstrated that cavitation could be utilized as a tool to purposefully modify the surface characteristics of these materials (in other worlds increase their surface roughness in a controllable fashion) in the micro-and nano-levels [52,53]. The relation between the behavior of the cavitation erosion process and the geometrical parameters of the generator (e.g.…”
Section: Micro-and Nano-scale Materials Characterizationmentioning
confidence: 99%
“…We demonstrated that cavitation could be utilized as a tool to purposefully modify the surface characteristics of these materials (in other worlds increase their surface roughness in a controllable fashion) in the micro-and nano-levels [52,53]. The relation between the behavior of the cavitation erosion process and the geometrical parameters of the generator (e.g.…”
Section: Micro-and Nano-scale Materials Characterizationmentioning
confidence: 99%
“…On the other hand, the destructive power of cavitation can be deliberately used to modify and enhance the surface or mechanical properties of target materials, e. g. for cleaning, cutting or peening with relatively low energy consumption. Cavitating water jets have received much attention also in the environmental industry for the possibility to use them for the decomposition of toxic substances and the water treatment [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Until now many experimental --------------studies on cavitating water jets have been made concerning jet driven pressure, shape and size of a nozzle, cavitation number, etc. [1,2,[5][6][7]. However, the structure of the cavitating jet and the behavior of the unsteady cavitation bubbles are still in question, mostly due to the difficulty to observe the interior of cavitating flows [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of the working conditions such as geometrical and hydrodynamical conditions is an important process to intensively utilize the jet destructive power (cavitation destructive power). The cavitating water jets have been widely utilized for cleaning of complicated mechanical products, cutting of solid materials, and surface improvement of materials in various industry fields [1][2][3][4]. It has received much attention also in the environmental industry for the possibility of applications to the decomposition of toxic substances and purification of sewage [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%